A new sebecid mesoeucrocodylian from the Rio Loro Formation (Palaeocene) of north-western Argentina - Pol, Diego (2011)
A new basal mesoeucrocodylian, Lorosuchus nodosusgen. et sp. nov., from the Palaeocene of north-western Argentina is presented here. The new taxon is diagnosed by the presence of external nares facing dorsally, completely septated, and retracted posteriorly, elevated narial rim, sagittal crest on the anteromedial margins of both premaxillae, dorsal crests and protuberances on the anterior half of the rostrum, and anterior-most three maxillary teeth with emarginated alveolar margins. This taxon is most parsimoniously interpreted as a bizarre and highly autapomorphic basal member of Sebecidae, a position supported (amongst other characters) by the elongated bar-like pterygoid flanges, a laterally opened notch and fossa in the pterygoids located posterolaterally to the choanal opening (parachoanal fossa), base of postorbital process of jugal directed dorsally, and palatal parts of the premaxillae meeting posteriorly to the incisive foramen. Lorosuchus nodosus also shares with basal neosuchians a suite of derived characters that are interpreted as convergently acquired and possibly related to their semiaquatic lifestyle. The phylogenetic analysis used for testing the phylogenetic affinities of L. nodosus depicts Sebecidae as the sister group of Baurusuchidae, forming a monophyletic Sebecosuchia that is deeply nested within Notosuchia. Alternative phylogenetic placements of Sebecidae, such as the recently proposed affinities with peirosaurids, were also evaluated within the context of the present data matrix and found to be only marginally suboptimal. © 2011 The Linnean Society of London.